Guía para el análisis estructural no lineal de puentes en Colombia (2021)
This document is intended to provide a series of recommendations and processes for modeling and analyzing single-span and multi-span bridge systems subjected to seismic loads, in order to correctly evaluate the nonlinear behavior of the system and its components. Also, a series of examples will be presented in order to illustrate these recommendations applied during the use of structural modeling software. It should be noted that some of the recommendations presented can be extended to other bridge typologies; however, it is left to the engineer's judgment to refer to the literature for scenarios other than those of this scope. Also, it is important to mention that the emphasis of this paper is the implementation of nonlinear analysis for the estimation of the demand on a bridge structure, but not for the evaluation of the capacity for design purposes.